96=6(w+8)

Simple and best practice solution for 96=6(w+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 96=6(w+8) equation:



96=6(w+8)
We move all terms to the left:
96-(6(w+8))=0
We calculate terms in parentheses: -(6(w+8)), so:
6(w+8)
We multiply parentheses
6w+48
Back to the equation:
-(6w+48)
We get rid of parentheses
-6w-48+96=0
We add all the numbers together, and all the variables
-6w+48=0
We move all terms containing w to the left, all other terms to the right
-6w=-48
w=-48/-6
w=+8

See similar equations:

| 6-4x=-48 | | 22-2q=10 | | -6.75+3.68=x | | 5x-9=-45 | | -9=27-11p=13p | | 3^4×3^a=3^-9 | | 6^x=162 | | 5x-9=-15 | | 7(u+5)=49 | | (x^2)+4x=5 | | 0,3x-0,7=-1,7+1,3x | | z/9+31=39 | | (x+5)^2=81 | | 4x^2-2-3=0 | | (25/81)^2x+1=(729/125)^-3+1 | | 5b+9=3b-1 | | 5x-4=-3x+20+(x-1) | | 4-3×(x-2)=2x | | 40.5x=25 | | 2x^2-80=162 | | -3=24+-9d | | -2y+7y+4=0 | | 3x^2+30=-138 | | g/3+10=3 | | -7(n+2)=-6n-8 | | h/6+3=-1 | | 3/4j+2/5=-22/10 | | -20-2n=5(-5n-4)-2 | | 1=p/7-2 | | -0.5(4+x)=(-1.3) | | −15+n=9 | | g/6-62=-54 |

Equations solver categories